Effect of Organo-mineral Fertilization on the Growth, Yield and Economic Profitability of Bean (Phaseolus vulgaris) in Eastern DRC: Effet de la fertilisation organo- minérale sur la croissance, le rendement et la rentabilité économique de haricot (Phaseolus vulgaris) à l’Est de la RDC - Z.P, Chakirwa; M.I., Murhi; K.C, Aksanti; F.C., Masirika; N.E, Banyanga; A.K, Lubobo, (International Journal of Scientific Research and Management (IJSRM), 2019)
In the face to low fertility existing in tropical soils, farmers in the Eastern Congo need cost-effective Soil Fertility Management (SFM) technologies to address the problem of low crop yields, which are particularly pronounced in grain legumes. This study assessed the financial returns associated with different SFM trials conducted on common bean grain in eastern Congo. Benefit-cost ratio analysis based on experimental data identified organic and mineral fertilizer technologies for common bean production. Two fields experiment were conducted at the Crop Research (INERA/Mulungu) and Walungu district (Ikoma). The experimental design was split plot with four replications. The main plot was the different time of application (2, 3 and 4 weeks after sowing) and the sub plot were the organic and inorganic fertilizers (40 N kg ha-1, 60 P2O5 ha-1 and 5 t Fumier ha-1) compare to an absolute control (0:0 N:P kg ha-1 and 0 t manure ha-1). The RWR21-54 was the variety used. N was applied as urea, P was applied as triple superphosphate (TSP) and organic fertilizer was applied as cow manure. Plant height was significantly (p